2014
DOI: 10.3109/07420528.2014.957299
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and eating habits of bus drivers during the day and night

Abstract: The aim of this study was to compare anthropometry and food intake patterns in bus drivers working during the day and night. One hundred and fifty males (81 night workers and 69 day workers) participated in the study. Dietary intake was assessed using a validated semi-quantitative food frequency questionnaire. Measurements of height, weight, waist circumference (WC), systolic and diastolic blood pressure, blood glucose, and lipid profile were obtained. A significant difference between groups was observed for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
1
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 44 publications
5
81
1
24
Order By: Relevance
“…Shift workers were also found to have a lower intake of fruits and vegetables (17,18), fiber (19) and some vitamins and minerals (eg, vitamin B, C, magnesium) (19) than day workers. In contrast, one study has shown a higher consumption of fruits for shift workers in comparison with day workers (20), and other studies showed no differences for fruits and vegetables (21), vitamin C (18) and fiber (18,22).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Shift workers were also found to have a lower intake of fruits and vegetables (17,18), fiber (19) and some vitamins and minerals (eg, vitamin B, C, magnesium) (19) than day workers. In contrast, one study has shown a higher consumption of fruits for shift workers in comparison with day workers (20), and other studies showed no differences for fruits and vegetables (21), vitamin C (18) and fiber (18,22).…”
mentioning
confidence: 76%
“…Most of these studies also lacked adjustment for major confounders, such as age (13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(24). Another important drawback is that the available studies focused on single nutrients or foods (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). For a comprehensive evaluation of differences in dietary intake, it is important to study dietary patterns because different nutrients and foods have additive and synergistic interactions (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of twenty-eight Brazilian shift workers found circadian rhythmicity of energy consumed by night workers but only during the summer (26) . A study on anthropometry and food intake patterns in bus drivers in Brazil reported higher proportions of inappropriate feeding practices, excess weight and abdominal obesity amongst drivers who worked night shifts (27) . So far, few studies have specifically investigated how consuming at a particular time of day relates to overall dietary intake in human subjects (28,29) .…”
Section: Shift Workers Disease Risk and Dietary Patternsmentioning
confidence: 99%
“…Studies presented in this Special Issue provide new evidence of possible underlying mechanisms. Balieiro et al (2014) compared anthropometry and food intake patterns in bus drivers working during the day and night and found a high prevalence of inappropriate feeding practices, excess weight and abdominal obesity among drivers of both groups, but most of the observed problems were more associated with drivers on night work than day work. These results suggest that a night work schedule can lead to nutritional and metabolic problems that are associated with high morbidity and mortality, such as obesity and its associated comorbidities.…”
Section: Health and Working Timementioning
confidence: 99%